Sosialisasi Dasar UMKM Berbasis Community Engagement Approach untuk Merumuskan Solusi Tantangan Usaha di Desa Utemungkur 1 Kecamatan Kolang, Tapanuli Tengah - Asyhari Abdillah Siregar; Sandi Sipahutar; M. Dimas Arif; Ahmad Syarqawi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The economic potential of Utemungkur 1 Village, Kolang District, Central Tapanuli Regency is still not optimal due to traditional business management and low financial literacy of MSMEs. This service activity aims to identify the main problems of village MSMEs and formulate solutions through basic socialization of MSMEs based on a community engagement approach. The method used is descriptive qualitative with a participatory approach through Focus Group Discussion (FGD) involving MSME actors, farmers, and fishermen. The results of the activity show problems in the form of mixing business and personal finance, low product added value, and limitations of digital marketing. The solutions formulated include the implementation of simple cash books, the use of community social media, and the initiation of the formation of Joint Business Groups (KUB). Early indicators of success can be seen from the increased understanding of financial recording and participants' commitment to business development. This activity encourages changes in the mindset of the community towards a growth mindset and strengthens the sustainability of the village economy based on participation.